Mindset Wirausaha: Berani Memulai Dan Tidak Takut Gagal - Dwi Maharani Putri; Erni Setyawati; Siti Nur Hidayanti; Veta Lidya Delimah Pasaribu (CV. ITTC INDONESIA, 2025)
Entrepreneurship is one of the main pillars of national economic development. However, the number of entrepreneurs in Indonesia remains relatively low compared to developed countries, partly due to the lack of entrepreneurial mindset among the younger generation. Many students and young people have creative ideas but hesitate to realize them due to fear of failure. A healthy entrepreneurial mindset emphasizes the courage to start, readiness to face risks, and the ability to turn failures into learning processes.This Community Service Program (PKM), conducted at SMA Pelita Bangsa, carries the theme “Entrepreneurial Mindset: Courage to Start and Not Afraid of Failure.” The program aims to instill entrepreneurial mindset from an early age so that students are more courageous in taking initiatives and view failure as a natural part of the journey toward success.The method used was Participatory Action Research (PAR) through observation, seminars, group discussions, case studies, and simple business simulations. The results indicate an increase in students’ understanding of entrepreneurial mindset, the growth of motivation to start small-scale ideas, and a change in perception toward failure. Prior to the program, 70% of students admitted being afraid of failure, while after the program, 80% declared readiness to try small businesses despite limited resources.This PKM is expected to serve as an effective learning model for building entrepreneurial mentality among high school students, while also contributing to the strengthening of the national entrepreneurship ecosystem from an early stage.